SAT0070 Patients with Early Rheumatoid Arthritis Treated with Remission Induction Treat-To-Target Regimens Report Important Early and Lasting Health Improvement: Results from The Carera Trial. (15th July 2016) - Van der Elst, K.; De Cock, D.; Stouten, V.; Joly, J.; Moons, P.; Verschueren, P.; Westhovens, R.
Abstract : Background: Patients' and healthcare providers' perceptions about treatment success can differ. Patient-reported health is therefore an important parameter to consider in daily care, especially in early rheumatoid arthritis (ERA), a disease stage where major health improvements can be realized, and patient adjustment is fully in progress. Objectives: To explore patient-reported health of persons with ERA within the first treatment year. Methods: The CareRA trial is a RCT rooted in daily practice, comparing remission induction treat-to-target regimens in ERA patients stratified in risk groups based on classical prognostic markers: in the high-risk group, patients were randomized to 1/3 intensive combination therapies with moderate-to-high-dose glucocorticoid bridging; in the low-risk group, patients were randomized to MTX monotherapy or MTX with moderate dose glucocorticoid bridging. The Short-Form 36 (SF36) questionnaire was used to assess 8 health dimensions at treatment initiation (BL), 4 months (W16) and 1 year (W52) later. Missing data were handled according to the SF36 user's manual. Differences in patient-reported health between risk and treatment groups, and between patients in remission (DAS28-CRP <2.6) or not were tested with Mann-Whitney U or Kruskal-Wallis. Results: Participants (n=379) shared characteristics with a typical ERA population; 66.2% was in remission at W16. The SF36 scores improved in all treatment groups at W16 and no differences between or within risk groups were observed, except for the general health dimension, which differed at W16 (p<0.001) and showed a different evolution (p=0.047) across the high-risk treatment arms. At W52, only the physical functioning score differed across the low-risk treatment arms (p=0.024). The largest health improvement was seen over the first 4 treatment months, while scores remained stable up to W52. The largest mean improvements were observed within physical health domains, e.g. "role physical" (30.84±45.07); but patients also reported progress in the mental health dimensions, e.g. "vitality" (10.44±19.39). Nevertheless, some participants did not report any improvement, e.g. 26 patients (8.52%) perceived no change in "physical functioning" after 4 months and 36 patients (11.80%) reported lower scores (mean change = -12.31±15.31), regardless of being in remission or not at W16 (p=0.93). Patients in remission at W16 scored significantly better for "mental health" (p<0.001) at W16, and for "role emotional" (p<0.001) at W16 and in terms of 4-month change (p=0.01). Conclusions: In our ERA population, important improvement in patient-reported health was seen at W16 lasting up to W52. Perceived health hardly differed between risk and treatment groups, which could be expected within a treat-to-target approach. Despite substantial improvements at group level, some patients did not perceive progress. Our future research will explore this particular subset, including also psychosocial health determinants, as these patients are likely to benefit from more tailored care interventions. Disclosure of Interest: None declared